Opportunities for building resilience and lessons for navigating risks: Dams and the water energy food nexus. Issue 1 (3rd May 2017) - Matthews, Nathanial; McCartney, Matthew
Abstract : After a hiatus through the 1990s and the early part of this century, rising energy demand, new private sector financing options and countries pursuing food security, modernization and economic growth have spurred a new era of large dam development. Currently an estimated 3700 dams are planned or under construction globally (Zarfl et al ., [2015] 77, 161–170). Many of the challenges faced in the context of the water‐energy‐food nexus are brought into sharp focus by large dam construction. Dams can safeguard food production, provide an important source of income and relatively cheap electricity, and can have direct and indirect benefits for poor people. Too often, however, they have created significant and poorly mitigated environmental and social costs (WCD, [2000] London: Earthscan Publications Ltd). Adverse impacts on ecosystem services caused by dam construction can have profound implications for the health, resilience and livelihoods of the poor. This article explores the challenges facing decision makers with regards to building resilience and navigating risk within the water‐energy‐food nexus and dams. It draws from two progressive case studies, one in Africa and one in Asia, to highlight lessons learned from nexus approaches including the need for meaningful participation, transparency in decision making, and valuing ecosystem services. The case studies examined contain relevant lessons for global agreements including the Sustainable Development Goals and the Paris Agreement because unlike the Millennium Development Goals, they are expected to address interlinkages and tradeoffs across the nexus. The implications of the increasing trend of public private partnerships to finance, build, and operate hydropower dams is discussed. The article concludes by demonstrating that although mitigating impacts across the nexus and social‐ecological resilience presents challenges and requires overcoming complexity, the need to tackle these is greater than ever . © 2017 American Institute of Chemical Engineers Environ Prog, 37: 56–61, 2018